2016
DOI: 10.1007/s10456-016-9516-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of endothelial proliferation with the magnitude of weight loss during calorie restriction

Abstract: Direction and magnitude of changes in serum-induced endothelial cell proliferation identifies patients with the greatest weight loss in response to modest calorie restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…They observed that patients with a "thrifty" phenotype (economic and energy saving) could distribute more energy for cell proliferation and lose less weight during CR, while patients with a "spendthrift" phenotype (wasteful and energy spending) would spend less energy for the cell proliferation and lost more weight after CR [91]. Accordingly, we observed that individuals who had lost more weight exhibited a decrease in cell proliferation (for quantitative data see [78]). We documented that a moderate CR in obese subjects changes the endothelial genes expression profile involved in the cell cycle [78].…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…They observed that patients with a "thrifty" phenotype (economic and energy saving) could distribute more energy for cell proliferation and lose less weight during CR, while patients with a "spendthrift" phenotype (wasteful and energy spending) would spend less energy for the cell proliferation and lost more weight after CR [91]. Accordingly, we observed that individuals who had lost more weight exhibited a decrease in cell proliferation (for quantitative data see [78]). We documented that a moderate CR in obese subjects changes the endothelial genes expression profile involved in the cell cycle [78].…”
Section: Discussionmentioning
confidence: 59%
“…Accordingly, we observed that individuals who had lost more weight exhibited a decrease in cell proliferation (for quantitative data see [78]). We documented that a moderate CR in obese subjects changes the endothelial genes expression profile involved in the cell cycle [78]. Similarly, Ellsworth et al have recently revealed significant changes in peripheral blood gene expression patterns, including those involved in cell cycle in obese patients undergoing intensive long-term lifestyle modifications.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations